2005
DOI: 10.1111/j.1574-0862.2005.00351.x
|View full text |Cite
|
Sign up to set email alerts
|

The conditions of collective action for local commons management: the case of irrigation in the Philippines

Abstract: We examine factors affecting the success and failure of collective action toward the management of local commons. Using cross-section survey data on the activities of irrigators' associations in the Philippines, regression analysis is conducted to identify factors underlying the success and failure in farmers' organizing collective action for the maintenance and operation of irrigation systems. We find that collective action is difficult to organize where (a) water supply is uniformly abundant; (b) water suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(122 citation statements)
references
References 18 publications
9
97
3
Order By: Relevance
“…The result also shows that users of older groups are more successful in collective maintenance than newer groups (model II). Our result is consistent with the findings of Fujiie et al (2005) and Meinzen-Dick et al (1997). But, Ternstrom (2003) found that the age of the organization has no statistical significance on the level of collective action.…”
Section: B) Characteristics Of the User Groupssupporting
confidence: 83%
See 2 more Smart Citations
“…The result also shows that users of older groups are more successful in collective maintenance than newer groups (model II). Our result is consistent with the findings of Fujiie et al (2005) and Meinzen-Dick et al (1997). But, Ternstrom (2003) found that the age of the organization has no statistical significance on the level of collective action.…”
Section: B) Characteristics Of the User Groupssupporting
confidence: 83%
“…For instance, some scholars disagree on variations in the physical characteristics of resources like scarcity, size, and proximity to markets, and how they affect the likelihood of collective action (e.g., Wade, 1987;Bardhan, 1993;Meinzen-Dick et al, 2002). Some researchers debate the importance of variations in the characteristics of resource users such as age of the resource users and salience of the resource to their livelihoods (Fujiie et al, 2005;Balland andPlatteau, 1996 andWade, 1987), while Ostrom et al, 1994;Poteete and Ostrom (2004) stress the importance of face-to-face communication. Tang (1992) broadly subdivided the factors into three categories: (i) physical and technical characteristics of the resource; (ii) characteristics of the users group and (iii) attributes of institutional arrangements.…”
Section: Theory and Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Not all actors in any given community, however, are eligible for these programs. While the subsidy programs mainly support the investment efforts of individual farmers, banks typically 6 While it is not believed that one can draw inferences from descriptive tables on causality, the work in the Phillipines by Fujiie et al (2005) show that water scarcity does lead to institutional changes in the water sector. In other work using data from China in both the surface water sector (Huang Q, Msangi S, Wang J, Huang J, Contract Water Management Reform and the Choice of Contractual Form in China, Center for Chinese Agricultural Policy, Chinese Academy of Sciences, Beijing, unpublished, 2005) and the groundwater sector (Wang et al 2005b), econometric analysis is used to show that causality can be determined.…”
Section: Privatization Of Tubewell Ownershipmentioning
confidence: 99%
“…For instance, Fujiie et al (2005) noted that service of national irrigation systems deteriorated after the reduction in state agencies' operation and maintenance activities because irrigators in south and southeast Asia could not meet all the costs of operation and maintenance from their farming activities. Similarly, smallholder irrigation schemes in South Africa were planned and established following a centralised state design system (Fanadzo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%